The field descent method - Bernhard, Schmidt. (2009)
We obtain a broadly applicable decomposition of group ring elements into a "subfield part" and a "kernel part". Applications include the verification of Lander's conjecture for all difference sets whose order is a power of a prime >3 and for all McFarland, Spence and Chen/Davis/Jedwab difference sets. We obtain a new general exponent bound for difference sets. We show that there is no circulant Hadamard matrix of order v with 4<v<548, 964, 900 and no Barker sequence of length l with 13 < l < 10^22.